MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DENGAN MODEL PEMBELAJARAN PAKEM PADA MATERI KETENAGAKERJAAN DI KELAS XI IPS SMA NEGERI 1 O’O’U - Laia, April (Universitas Nias Raya, 2024)
The purpose of this study is to describe the learning model PAKEM model can increase the learning motivation of 25 grade XI IPS students of SMA Negeri 1 O’O’U, in the basic competencies of Employment. The results of observations before improving learning in grade XI IPS, in this subject obtained the average student score is ≤ 70 while KKM 70. Based on these conditions, teachers conduct research to improve learning through the PAKEM approach. Therefore, researchers try to implement PAKEM learning strategies, which are learning strategies that can feature active, creative, effective and fun learning. The procedure is used in the form of cycles, each cycle consists of four stages, namely planning, implementation, observation, reflection. This research guideline uses observation instruments and tests of student learning outcomes in each cycle. The results of the study were obtained, there was an increase in student learning motivation in classroom learning. This is proven by the increase in learning outcomes from cycle I to cycle II, namely from an average value of 73.23 (cycle I) to an average value of 85.25 (cycle II).